2021
DOI: 10.1159/000514056
|View full text |Cite
|
Sign up to set email alerts
|

Whether Adding Vitamin D to Tadalafil 5 mg Treatment Is Useful in Patients with Erectile Dysfunction and Vitamin D Deficiency?

Abstract: <b><i>Introduction:</i></b> Numerous factors such as endothelial disease and hormonal disorder cause the development of erectile dysfunction (ED). However, the relationship between vitamin D deficiency (VDD) and ED is unclear. Moreover, the benefit of vitamin D replacement on ED patients with VDD is uncertain. As far as we know, there is no study yet in the literature regarding the addition of vitamin D to phosphodiesterase type 5 inhibitors in the treatment of ED patients with VDD. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…On average, men with ED are approximately 60 years old and suffer from chronic comorbidities in approximately 80% of cases, while 94% have a regular comedication intake [22]. In fact, 88% receive pharmacological treatment for their ED, mainly PDE5is such as tadalafil [22][23][24]. Unfortunately, 37% of patients do not notice any effects of PDE5is, while 49% discontinue the treatment because of side effects or ineffectiveness [25].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…On average, men with ED are approximately 60 years old and suffer from chronic comorbidities in approximately 80% of cases, while 94% have a regular comedication intake [22]. In fact, 88% receive pharmacological treatment for their ED, mainly PDE5is such as tadalafil [22][23][24]. Unfortunately, 37% of patients do not notice any effects of PDE5is, while 49% discontinue the treatment because of side effects or ineffectiveness [25].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…To date, only a few studies have evaluated vitamin D administration as a possible therapeutic strategy to treat patients with ED [ 164 , 165 ]. Indeed, a retrospective study demonstrated a greater improvement in erectile function in patients with ED treated with tadalafil and vitamin D (4000 IU/day) compared to those treated with tadalafil alone [ 164 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study, the relationship between the effect of Sildenafil 100 mg and Vitamin D level was evaluated and it was concluded that a 25(OH) vitamin D level in the normal range was important for the success of Sildenafil (Mostafa et al, 2019). In another study, Tadalafil 5 mg + Vitamin D replacement therapy was shown to have better results compared to the patients taking Tadalafil 5 mg alone (Demirci et al, 2021). The present study differs in that patients who did not respond to Tadalafil 5 mg treatment were included in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that patients who did not respond to sildenafil citrate treatment, which is another PDE-5 inhibitor, had lower Vitamin D levels (Mostafa et al, 2019). In the recent study, it was reported that Vitamin D supplementation with Tadalafil 5 mg had positive results on ED (Canguven et al, 2017;Demirci et al, 2021). The effect of Vitamin D supplementation has not been evaluated in patients who do not respond to Tadalafil treatment.…”
Section: Introductionmentioning
confidence: 99%